Analisis potensi energi matahari di Institut Teknologi Sumatera: Pertimbangan Faktor Kelembaban dan Suhu - Mohamad Samsul Anrokhi; Mahardika Yoga Darmawan; Ali Komarudin; Kiki Kananda; Deska Lismawening Puspitarum (Journal of Science and Applicative Technology, 2019)
Indonesia's electricity needs are increasing in line with increasing population and living standards. Renewable energy is an alternative in avoiding dependence on conventional PLN electricity. This research is a further study of solar energy as an alternative energy to meet the electricity needs of Institut Teknologi Sumatera (ITERA) which always increases every year with the increasing number of students and the infrastructure of lecture infrastructure. Research on the potential of solar energy at the ITERA has been carried out before using conventional methods. This study further examines the potential of solar energy by considering various factors. This study uses solar cells with 100 WP specifications and uses Arduino UNO instrumentation to facilitate the measurement of current and voltage automatically which can be stored directly in memory cards. Based on the measurement results obtained a maximum power value of 66 watts that occurs at 11:00 and 12:00 WIB. Keywords: Solar cell, solar energy